Mechanics IUTAM USNC/TAM A History of People, Events, and Communities - Herakovich, Carl T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a detailed history of the United States National Committee on Theoretical and Applied Mechanics (USNC/TAM) of the US National Academies, the relationship between the USNC/TAM and IUTAM, and a review of the many mechanicians who developed the field over time. It emphasizes the birth and growth of USNC/TAM, the birth and growth of the larger International Union of Theoretical and Applied Mechanics (IUTAM), and explores the work of mechanics from Aristotle to the present. Written by the former Secretary of USNC/TAM, Dr. Carl T. Herakovich of the University of Virginia, the book profiles luminaries of mechanics including Galileo, Newton, Bernoulli, Euler, Cauchy, Prandtl, Einstein, von Kármán, Timoshenko, and in so doing provides insight into centuries of scientific and technologic advance. Profiles the applied mathematicians and engineers who developed the field of mechanics in the context of the establishment of the USNC/TAM and the IUTAM Details the relationship between USNC/TAM and IUTAM Traces the significant developments in the field of mechanics Examines the development of the USNC/TAM from its birth to the present.
Acknowledgements -- Preface -- Mechanics: An Engineering Science -- Brief History Of Mechanics -- The Giants Of Mechanics -- Ancient Greece (Bc) -- The Renaissance -- Industrial Revolution -- Paris And École Polytechnique -- Technological Revolution -- Major Developments In Mechanics -- Mechanics At Göttingen -- International Research Council -- The Innsbruck Conference -- International Applied Mechanics Congresses -- Mechanics In The United States -- Land Grant Colleges -- National Academy Of Sciences (Nas) -- First Flight -- National Advisory Committee For Aeronautics (Naca) -- National Research Council (Nrc) -- Immigrants To United States -- Other Immigrants To The United States -- Asme Applied Mechanics Division -- International Congresses - American Involvement -- International Union Of Theoretical And Applied Mechanics -- IUTAM General Assembly -- IUTAM Bureau -- USNC/TAM -- USNC/TAM Time Line -- The Independent Years -- A Committee Of The National Academy Of Sciences -- USNCTAM Constitution And Bylaws -- USNCTAM Member Societies -- USNC/TAM Members -- USNC/TAM Officers -- USNC/TAM Chairs -- Secretaries Of The USNC/TAM -- USNC/TAM In IUTAM Leadership Positions -- USNC/TAM Diversity -- Academic Genealogy -- Gender Diversity -- Ethnic And Racial Diversity -- Age Diversity -- Mechanics Specialty -- USNC/TAM Activities -- Meetings With Governmental Agency Representatives -- Scordim Reports -- U. S. Congress Of Applied Mechanics -- IUTAM Symposia And Summer Schools -- International Congresses Of Applied Mechanics -- Travel Grants To International Congresses -- International Prizes -- USNC/TAM Operations Manual -- Finances -- NSF Funding -- USNC/TAM Private Funds -- Relations With The National Academy Of Sciences -- Strategic Planning -- Epilogue -- Appendices -- Appendix A - IUTAM Bureau Members -- IUTAM Bureau - - (Color Coded For Some Countries) -- Appendix B - USNC/TAM Constitution -- Appendix C USNC/TAM By-Laws -- I.Participating Societies -- Ii.Members -- Iii.Executive Committee -- Iv.Operations -- V.Voting -- Vi. Amendments Of The By-Laws -- Appendix D -Societies Represented In USNC/TAM -- Appendix E - USNC/TAM Membership -- Appendix E. USNC/TAM Membership By Year -- Appendix E. - USNC/TAM Officers -- Appendix E. - USNC/TAM Society Representatives -- Appendix E. - USNC/TAM Members-At-Large -- Appendix E. - U. S. Congress Chairs -- Appendix F - USNC/TAM Members In IUTAM Positions -- U. S. IUTAM Members-At-Large (Personal Members) -- U. S. Members Of The IUTAM Bureau -- U.S. Members Of The IUTAM Congress Committee -- U. S. Members Of The IUTAM Congress Executive Committee -- U. S. Members Of The IUTAM Fluids Symposium Panel -- U. S. Members Of The IUTAM Solids Symposium Panel -- Appendix G U.S. Members Of The IUTAM General Assembly -- Appendix H - Academic Genealogy -- Appendix H USNC/TAM Member Academic Genealogy -- Appendix I - U.S. National Congress Proceedings -- Appendix J U. S. Chaired IUTAM Symposia & Summer Schools -- Appendix K - Ictam Congresses -- Appendix L - USNC/TAM Resolutions -- Frenkiel Resolution -- Hodge Resolution -- Herakovich Plaque -- Appendix N - Abbreviations -- USNC/TAM Societies -- Academies, Committees And Government Organizations -- People Index.
Keywords: Mechanics, Applied; Engineering; Mechanics; Physics; Astronomy; Technology; History; Science -- History; Engineering Mechanics; Technology and Engineering; Classical Mechanics; Physics and Astronomy; History of Technology; History of Science